2011
DOI: 10.1128/jvi.01986-10
|View full text |Cite
|
Sign up to set email alerts
|

Successful Propagation of Flavivirus Infectious cDNAs by a Novel Method To Reduce the Cryptic Bacterial Promoter Activity of Virus Genomes

Abstract: Reverse genetics is a powerful tool to study single-stranded RNA viruses. Despite tremendous efforts having been made to improve the methodology for constructing flavivirus cDNAs, the cause of toxicity of flavivirus cDNAs in bacteria remains unknown. Here we performed mutational analysis studies to identify Escherichia coli promoter (ECP) sequences within nucleotides (nt) 1 to 3000 of the dengue virus type 2 (DENV2) and Japanese encephalitis virus (JEV) genomes. Eight and four active ECPs were demonstrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 64 publications
3
109
0
1
Order By: Relevance
“…The vRNA level of 91.93 also showed a moderate reduction of ca. 50% at 48 to 72 h, which is in agreement with previous findings (28). The viral loads in the supernatants of the WT-, 75.78-, and S3X-transfected BHK-21 cells were compared.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The vRNA level of 91.93 also showed a moderate reduction of ca. 50% at 48 to 72 h, which is in agreement with previous findings (28). The viral loads in the supernatants of the WT-, 75.78-, and S3X-transfected BHK-21 cells were compared.…”
Section: Resultssupporting
confidence: 80%
“…Enhancer-like elements (DB1 and DB2) had only been found in the 3=UTR (24,26) until recently, when a cis-acting enhancer element, SL6, was discovered in the capsid-coding region of tickborne flavivirus (27). The results from different groups (28)(29)(30) also indicate that the region downstream of the DENV 5=CS regulates vRNA replication, but the mechanism by which this occurs is unknown. In this study, using a combination of bioinformatic, biochemical, and reverse genetic approaches, we identified a novel cis-acting element, the downstream of 5=CS pseudoknot (DCS-PK), in the capsid-coding region, which is conserved in mosquitoborne flaviviruses.…”
Section: T He Flavivirus Genus Contains Numerous Important Agents Of mentioning
confidence: 79%
“…Preliminary studies indicated that full-length infectious clones were unstable in Escherichia coli (data not shown), likely due to cryptic prokaryotic promoters within the E and NS1 coding sequences (18). Therefore, we developed a two-plasmid system that would allow the 5= and 3= ends of the viral genome to be joined through unique ApaLI and SapI restriction enzyme sites in NS1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In general, cloning of the full-length cDNA of flavivirus downstream of either a T7/SP6 promoter or a eukaryotic RNA polymerase II promoter is sufficient to enable the recovery of progeny virus from the corresponding in vitro transcribed RNA or plasmid DNA. However, the cDNAs of flavivirus genomes are known to be toxic and unstable in common Escherichia coli hosts (16)(17)(18)(19)(20), which can be primarily attributed to the leaky expression of toxic viral proteins from the cryptic prokaryotic promoters in viral cDNA (19,20). This phenomenon has significantly hindered the development of flavivirus infectious clones (16)(17)(18)21).…”
mentioning
confidence: 99%